Synthesis of cadmium selenide thin films at low-temperature by simple chemical route and their characterization - Hankare, P. P.; Delekar, S. D.; Asabe, M. R.; Chate, P. A.; Bhuse, V. M.; Khomane, A. S.; Garadkar, K. M.; Sarwade, B. D. (Journal of Physics and Chemistry of Solids, 2006)
Crystalline CdSe thin film has been deposited using appropriate precursor solution containing cadmium sulfate octahydrate, tartaric acid, potassium hydroxide, ammonia and sodium selenosulfate. The effect of parameters such as bath composition, deposition temperature, pH of the solution, speed of the rotation and the specificity of complexing agent on growth process is studied. The `as-deposited' CdSe thin film was found to be red in color, specularly reflective and well adherent to the glass substrate. The crystalline phase of the deposited sample was hexagonal wurtzite-type. The analysis of optical absorption data shows energy band gap energy (E-g) 2.01 eV. The morphological study and compositional analysis of film sample have been discussed. The electrical resistivity of CdSe thin film was found to the order of 10(6) Omega cm. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: XRD